Analisis Pertumbuhan Ekonomi, Indeks Pembangunan Manusia, Inflasi, dan Upah Terhadap Kemiskinan - Moh Nur Khaqiqi; Tsalis Syaifudin (Departement of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri K.H Abdurrahman Wahid Pekalongan, 2021)
The purpose of this study was to determine the effect of predetermined vaiables on poverty. And looking for solutions to deal with poverty cases in Pemalang Regency. This research is included in the type of quantitative research. This research uses secondary data from BPS Pemalang. This study uses the Least Squares multiple linear regression analysis method whit the Eviews statistical tool. The results of this study indicate that the probability value is 0.000148, this value is less than 0.05, which means that economic growth, HDI, inflation, and wages simultaneously affect poverty in Pemalang Regency. Partially the HDI, inflation, and wages variables have a significant effect on poverty, meanwhile, the economic growth variable has an insignificant influence on poverty. Therefore, poverty is not only about the economy but also about the quality of human resource.